2000
DOI: 10.1006/cbir.2000.0581
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Expression of Small Intestine Extracellular Matrix Proteins in Streptozotocin‐induced Diabetic Rats

Abstract: Diabetes mellitus is characterized by anatomical and functional alterations of the intestinal tract. However, the aetiology of these disturbances remains unclear. The aim of the present work was to investigate the effects of diabetes on the expression of laminin-1 and fibronectin in the small intestine of Streptozotocin (STZ)-induced diabetic rats. The Western immunoblotting of the extracts from the small intestine revealed that experimental diabetes resulted in a marked increase in the intensity of the bands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Increased muscle weight in the small intestine was also noted in a subsequent study (30). Furthermore, in the small intestine, proliferation of epithelial cells and hypertrophy of the mucosa have been observed in conjunction with alterations of the smooth muscle layer in rat duodenum (35). The development of rhythmic contractions in both control and diabetic colon was primarily due to myogenic mechanisms and/or ICC.…”
Section: Discussionmentioning
confidence: 60%
“…Increased muscle weight in the small intestine was also noted in a subsequent study (30). Furthermore, in the small intestine, proliferation of epithelial cells and hypertrophy of the mucosa have been observed in conjunction with alterations of the smooth muscle layer in rat duodenum (35). The development of rhythmic contractions in both control and diabetic colon was primarily due to myogenic mechanisms and/or ICC.…”
Section: Discussionmentioning
confidence: 60%
“…AGEs are generated by sequential non-enzymatic glycation of protein amino groups and by oxidation reaction [21]. Studies on diabetes and aging show that AGEs cause the cross-linking of collagen molecules responsible for basement membrane thickening and the loss of matrix elasticity [22][23][24]. Sán-chez et al [23] demonstrated the expression of small intestinal extracellular matrix protein changes in STZinduced diabetic rats.…”
Section: Biomechanical Remodelling Of the Diabetic Colonmentioning
confidence: 99%
“…Studies on diabetes and aging show that AGEs cause the cross-linking of collagen molecules responsible for basement membrane thickening and the loss of matrix elasticity [22][23][24]. Sán-chez et al [23] demonstrated the expression of small intestinal extracellular matrix protein changes in STZinduced diabetic rats. Kandemir et al [25] found that colonic subepithelial collagenous thickening occurred in diabetic patients.…”
Section: Biomechanical Remodelling Of the Diabetic Colonmentioning
confidence: 99%
“…17 Specimens fixed in Bouin's solution were dehydrated through a graduated alcohol series and embedded in Paraplast. The sections were cut into 7-µm thick slices, deparaffinized and rinsed with PBS (pH 7.4).…”
Section: Immunohistochemistrymentioning
confidence: 99%